Immunocytochemical markers in stage I lung cancer: relevance to prognosis. - Pastorino, U; Andreola, S; Tagliabue, E; Pezzella, F; Incarbone, M; Sozzi, G; Buyse, M; Menard, S; Pierotti, M; Rilke, F (1997)
PURPOSE: This study investigated the frequency of the expression and prognostic significance of a panel of immunocytochemical markers in resected non-small-cell lung cancer (NSCLC). PATIENTS AND METHODS: A total of 515 cases of pathologic stage I NSCLC were analyzed. The median follow-up time of surviving patients was 102 months. The following immunocytochemical markers were tested: blood group A and precursors of blood antigens; laminin receptor; c-erbB1/epidermal growth factor receptor (EGFR) and c-erbB2/Neu; BCl2; p53; and angiogenesis. Kaplan-Meier estimates of survival and time to recurrence were calculated for clinical variables and biologic markers using the Cox model for multivariate analysis. RESULTS: The pathologic tumor extension (pT) represented the most powerful prognostic factor for survival (P = .0008) and time to recurrence (P = .0007). None of the immunocytochemical markers emerged as an independent predictive factor for survival. Bcl2-positive tumors showed a better time to recurrence (P = .03), but the difference lost statistical significance in the multivariate analysis. Of interest, in the group of 137 patients classified as pT1N0, both EGFR expression and nonangiogenic type of vascular pattern were associated with a poorer survival (P = .02). However, data derived from subset analysis must be interpreted cautiously. CONCLUSION: Our findings do not support a relevant prognostic role of immunocytochemical markers in NSCLC. The evidence is not sufficient to alter clinical practice or even to restrict clinical trials of adjuvant treatments to predefined biologic subsets of patients.